(untitled) (Journal of Health Sciences, 2014)
Introduction: Requirements to implement scientific knowledge in practice within the Swedish health and social care sectors have increased during the last decades. One of these networks was the Network for Eating and Nutrition that began in 2003. The aim of this study was to retrospectively evaluate how the Network for Eating and Nutrition has functioned during a period of ten years and in what way it has affected work practice.Methods: This is a descriptive qualitative study. Data sources for this study were meeting records collected over 10 years and two evaluation surveys (at five and 10 years). Participants were members of the Network for Eating and Nutrition (n=12 at five years and n=10 at 10 years). The manifest qualitative content analysis was used.Results: The Network for Eating and Nutrition was seen as offering support for personal and organisational knowledge development. Further aspects of support from the workplaces of the members and the significance for the work places were described. Further the Network for Eating and Nutrition reached out to care receivers by using specifically tailored education programmes and material. The Network for Eating and Nutrition results and recommendations were described as important references for the development of nutrition routines.Conclusion: Networks between organisations with different professional backgrounds can form a basis for knowledge exchange both for focus on the specific topic but also on how to work with quality improvement, i.e. evidence based practice.